Decision Support System for Teacher Performance Assessment Using the Weighted Product Method - Karyaningsih, Dentik (International Journal of Information Technology and Computer Science Applications, 2023)
The quality of teachers can be seen from the results of their performance assessment whether they have increased or vice versa. Therefore, an objective performance appraisal system is needed, in addition to reviewing performance results, the assessment system can also be a reference for determining the best teacher, so that teachers are more motivated in teaching. In making decisions on teacher performance evaluation at Pelita Insani Special Schools, they still experience problems when the process is done manually and the assessment system is less objective. So we need a Decision Support System that can produce the best alternative, can be done automatically and objectively. Practitioners This study produced a web-based decision support system that can provide alternative decision-making for school principals based on teacher performance results. By using the Weighted Product method. There are six criteria, namely: learning planning, implementing learning, assessing learning outcomes, training and guiding, additional assignments, and developing professional activities, then processed with data on teacher performance results with this method and produces teacher rankings which can be recommendations for decision making for school principals